A grammar of Skolt Saami - Feist, T
This thesis is a descriptive grammar of Skolt Saami, a Finno-Ugric language spoken primarily in northeast Finland by less than 400 people. The aim of this thesis is to provide an overview of all the major grammatical aspects of the language. It comprises descriptions of Skolt Saami phonology, morphophonology, morphology, morphosyntax and syntax. A compilation of interlinearised texts is appended. Skolt Saami is a phonologically complex language, displaying contrastive vowel length, consonant gradation, suprasegmental palatalisation and vowel height alternations. It is also well known for being one of the few languages to display three distinctive degrees of quantity; indeed, this very topic has already been the subject of an acoustic analysis (McRobbie-Utasi 1999). Skolt Saami is also a morphologically complex language. Nominals in Skolt Saami belong to twelve different inflectional classes. They inflect for number and nine grammatical cases and may also mark possession, giving rise to over seventy distinct forms. Verbs belong to four different inflectional classes and inflect for person, number, tense and mood. Inflection is marked by suffixes, many of which are fused morphemes. Other theoretically interesting features of the language, which are covered in this thesis, include (i) the existence of distinct predicative and attributive forms of adjectives, (ii) the case-marking of subject and object nominals which have cardinal numerals as determiners, (iii) the marking of negation with a negative auxiliary verb and (iv) the apparent verb-second phenomenon which is observed in clauses displaying an auxiliary verb. Skolt Saami is a seriously endangered language and it is thus hoped that this grammar will serve both as a tool to linguistic researchers and as an impetus to the speech community in any future revitalisation efforts.